Peran Pupuk Organik dalam Meningkatkan Efektivitas Pupuk NPK pada Bibit Kelapa Sawit di Pembibitan Utama - Sari, Vira Irma; ,, Sudradjat; ,, Sugiyanta (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
Main nursery is the first step affecting oil palm’s age and productivity. Good plant growth will produce high quality and yield of oil palm. The demand of oil palm seedlings for extensification and replantation increases continuously, and therefore this need to be supported by precise fertilization programs. The objectives of this experiment were to investigate the role of organic fertilizer and to obtain the best organic-NPK fertilizer combination in increasing the effectiveness of the use of NPK fertilizer for the growth of oil palm (Elaeis guineensis Jacq.) seedling in the main nursery. The experiment was conducted from December 2011 to September 2012 at IPB Teaching Farm Dramaga Bogor. The treatment was arranged in a factorial randomized block design with three replications. The first factor was amount of organic fertilizer consisted of 0:6, 1:6, 2:6, and 3:6 of the soil volume (6 kg). The second factor was NPK fertilizer rates, i.e., 0.0, 127.5, 255, and 382.5 g NPK per plant. The results showed that application of organic fertilizer increased the effectiveness of NPK fertilizer and could be a substitute for NPK fertilizer in oil palm seedlings. The best combination treatment was 2:6 (organic fertilizer:top soil) and 382.5 NPK g per plant with effectiveness of 158.9, 209.1 and 170.1 % for plant height, leaf number and stem diameter, respectively. The efficiency of N, P, and K application were 56.2, 11.1, and 29.0% for the same variables, respectively. Based on morphological variables, recommended rate of an NPK compound fertilizer 15-15-15 was in the range of 396.05 g per seedling for eight months. Recommended NPK were 7.00, 12.59, 37.58, 56.41, 36.74, 87.00, 86.60, and 72.97 g per seedling for first to eighth months, respectively.Keywords: chlorophyll, fertilizer recomendation, morphological and physiological response, nutrient balance